THE IMPACT OF SELF-CARE MANAGEMENT ON INTERDIALYTIC WEIGHT GAIN AMONG CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Mufarika; Eka So'emah; Agus Haryanto; Mulia Mayang Sari (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Patients with Chronic Kidney Disease (CKD) undergoing hemodialysis therapy frequently experience complications. A prevalent issue among these patients is Interdialytic Weight Gain (IDWG). Preliminary studies indicate a high incidence of IDWG among CKD patients undergoing hemodialysis at RSUD Syamrabu Bangkalan. This study aims to analyze the relationship between self-care management and Interdialytic Weight Gain in CKD patients undergoing hemodialysis. This study employed an analytical correlation design with a cross-sectional approach. The independent variable was self-care management, while the dependent variable was IDWG. The study population consisted of 106 CKD patients undergoing hemodialysis at RSUD Syamrabu Bangkalan, with a sample size of 83 respondents selected through purposive sampling. Data were collected using a self-care management questionnaire and IDWG observation sheets. Statistical analysis was performed using the Spearman Rank correlation test with a significance level of α= 0.05. The Spearman Rank test results for self-care management and IDWG yielded a r-value of 0.001 (α< 0.05) and a correlation coefficient (r) of (-0.369). There is a significant relationship between self-care management and Interdialytic Weight Gain. The correlation value indicates a weak (low) relationship between the two variables. Higher proficiency in self-care management enhances an individual's knowledge level and facilitates better control over weight gain or IDWG. Future researchers are encouraged to investigate other variables not yet explored, such as quality of life, knowledge levels, and family support, to further enrich data regarding interdialytic weight gain